Archaeological calibration of remagnetized volcanic rocks from pottery firing kilns in Cuentepec, Morelos, Mexico - H. López-Loera; S. L. López-Varela; A. M. Soler-Arechalde; J. A. González-Rangel; L. M. Alva-Valdivia (Geofísica Internacional, 2006)
Ethnoarchaeological research at the site of Cuentepec, Mexico includes experimental pottery dating in which social knowledge is obtained from archaeometric techniques. At Cuentepec, open kilns are used for firing pottery. Samples from volcanic rocks in the kilns were taken to verify the reliability of the magnetic direction in these rocks as compared with data from Teoloyucan Geomagnetic Observatory, near Mexico City. In the laboratory, forty-seven cores from eight hand oriented rock samples were drilled. Continuous susceptibility measurements at high temperature yield in most cases reasonably reversible curves with Curie points ranging from Ti-rich to Ti-poor titanomagnetite. The ratios of hysteresis parameters indicate that all samples fall in the pseudo-single domain grain size region, probably indicating a mixture of multidomain plus a significant amount of single domain grains. Isothermal remanent magnetization acquisition curves were very similar for nearly all samples. Saturation is reached in moderate fields of the order of 100-120 mT, which points to some spinels as remanence carriers. We conclude that the samples obtained from the inner part of the blocks in the kilns closer to the fire kept the most reliable records of the geomagnetic field.